2021
DOI: 10.1111/tbed.13968
|View full text |Cite
|
Sign up to set email alerts
|

Epidemic situation and control measures of African Swine Fever Outbreaks in China 2018–2020

Abstract: As of 21 April 2020, 176 ASF outbreaks have occurred in China. For each outbreak, an investigation was conducted, including historical data retrieval and traceability of potential contacts. The purpose of this study is to conduct a preliminary analysis of the data obtained from the outbreak investigations, including an investigation of the possible contributing factors of the spread of ASF in China. Based on the epidemic situation and the policies issued, the entire epidemic can be divided into three phases. 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 18 publications
1
45
1
1
Order By: Relevance
“…The scale of this disparity has been evidenced with the spread of ASF through Southeast Asia. In China, the proportional rate of outbreaks in smaller farms has been much greater than in medium or large farms ( 36 ). The resultant collapse of the smallholder farming sector, which produces more than 80 percent of China's pork, has created big “winners” from the crisis in the form of large pig production firms ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…The scale of this disparity has been evidenced with the spread of ASF through Southeast Asia. In China, the proportional rate of outbreaks in smaller farms has been much greater than in medium or large farms ( 36 ). The resultant collapse of the smallholder farming sector, which produces more than 80 percent of China's pork, has created big “winners” from the crisis in the form of large pig production firms ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…ASF was first described in Kenya in 1921 [ 1 ] and spread throughout sub-Saharan Africa ( www.ioe.int ). ASFVs are classified into different genotypes based on the 3′-end sequences of the B646L gene, which encodes the major capsid protein p72 [ 3 , 4 ]. To date, 24 different ASFV genotypes have been identified in Africa.…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, Georgia-07-like genotype II ASFV emerged in China, and spread to 15 other Asian countries ( www.oie.int ) [ 10–12 ]. This virus causes very acute disease with near 100% mortality, and has been prevalent in China for almost three years ( www.oie.int ) [ 4 , 10 , 12–14 ]. A subsequent surveillance study found that lower virulent genotype II ASFVs emerged in China in 2020 due to natural mutations in the genomes of the highly virulent viruses [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Investigations into ASF outbreaks in China have identified three phases, with outbreaks more likely to affect small farms. Spread has been linked with swill feeding and the movement of vehicles and personnel, rather than transportation of live pigs (Gao et al, 2021).…”
mentioning
confidence: 99%